TINJAUAN HUKUM PIDANA TERHADAP TINDAK PIDANA PENYALAHGUNAAN NARKOBA OLEH ANGGOTA MILITER (Studi Putusan Pengadilan Militer III-13 Madiun Nomor: 09-K/PM.III-13/AD/II/2012) - Hima Y.P, Candra; Puspaningtyas, Siska (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2013)
AbstractFlourishing drug offenses even actors as if do not want to know if there are criminal sanctions that would accompany the military is no exception. Military members who commit drug crimes, other offenses sentenced based on Narcotic Law, Military Court judge can impose additional punishment in the form of dismissal from military service or demotion. The research method used here is a normative legal research methods that use secondary data types. Secondary data obtained through the study of literature, such as a legal instrument in the form of legislation, books, publications of various organizations, reports and documents relating to the matter under investigation. Consideration of the results of research in military judge dropped criminal charges against the doers do not consider the amount of evidence, but considering the quality (class of drugs) and evidence that the defendant possessed narcotics offenses. Should the number of items of evidence to be considered in imposing the severity of criminal charges against the doers and not just because of the evidence obtained belong to one particular class of drugs.Keywords: crime, drugs, military